Nutrition Content of Murrah Buffalo's Milk Curd By Using Lime Juice (Citrus aurantifolia) - Hasnudi; Yunilas; E. Mirwandhono; N. Ginting; Yanti, S.D (Jurnal Peternakan Integratif, 2022)
. Dadih is the result of fermented milk made in bamboo and covered with banana leaves on top, then allowed to stand for approximately 24-48 hours. This study aims to determine the effect of various doses of lime juice (Citrus aurantifolia) in the manufacture of dadih on the nutritional content (water content, fat content, protein content, carbohydrates and pH).This research method used a completely randomized design (CRD) 4 treatments 5 replications. The treatments were dose of lime juice, namely P0 = 0% Control only buffalo milk without lime, P1 = 1% lime juice, P2 = 3% lime juice, P3= 5% lime juice. Based on the research results, it is known that the addition of 5% (10 ml) for every 200 ml of milk is the optimal treatment for water content, fat content, protein content, carbohydrates and pH.